Kontribusi Lokus Kendali, Regulasi Emosi, dan Harga Diri terhadap Tingkat Kesejahteraan Psikologis - Ahmad, Astiti Tenriawaru; Rasyid, Nurfajriyanti (INSIGHT: Indonesian Journal Social Studies and Humanities, 2025)
Abstract. Psychological well-being is a multidimensional construct crucial for human welfare. This study aims to analyze the influence of internal and external locus of control, emotion regulation, and self-esteem on psychological well-being. The sample consisted of 219 respondents. Linear regression analysis showed that the model explained 45.6% of the variance in psychological well-being (R² = 0.456). Self-esteem was the strongest predictor (β = 0.526, p < 0.001), followed by internal locus of control (β = 0.522, p < 0.001). External locus of control had a significant negative effect (β = -0.407, p = 0.002), while emotion regulation contributed minimally (β = 0.046, p = 0.042). The findings were validated with Spearman correlation, showing convergent validity. The findings imply that self-esteem and sense of internal control are the main determinants of psychological well-being among students. Keywords: psychological well-being, locus of control, self-esteem, emotion regulation